Novel curvilinear sprint test in basketball: reliability and comparison with linear sprint - Baena-Raya, A.; Díez-Fernández, D. M.; López-Sagarra, A.; Martínez-Rubio, C.; Soriano-Maldonado, A.; Rodríguez-Pérez, M. A. (The Journal of Strength and Conditioning Research, 2023)
This study (a) evaluated the reliability of a curvilinear sprint (CS) test to assess kinetic and kinematic outcomes in basketball players, (b) compared the kinetic and kinematic outcomes derived from curvilinear vs. linear sprints (LS), and (c) examined the association of both the CS and LS with change of direction (COD) performance. Thirty young basketball players (17 men and 13 women) competing at the national level (i.e., Spanish Basketball National League) performed a novel CS test around the 3-point line (the 3-point line CS test) to the right and left sides. The maximum and average values of acceleration (ACC), velocity (VEL), and centripetal force (CentF) were measured using Local Positioning System technology (WIMU PRO, Realtrack Systems S.L., Almería, Spain). All outcomes showed a high relative (intraclass correlations coefficient = 0.90) and absolute (coefficient of variation [CV] < 5%) reliability, except the maximal CentF to the right (CV = 5.41%) and left sides (CV = 7.72%). Linear sprints displayed higher ACC and VEL outputs compared with the 3-point line CS test (all p < 0.001). Both sprinting tests were very large to nearly perfect associated with COD performance (LS r range from -0.71 to -0.86; CS r range from -0.68 to -0.94; p < 0.001), and the curvilinear ACCmax was the kinematic outcome most strongly associated with COD performance (r range from -0.73 to -0.94). In conclusion, the 3-point line CS test is reliable to measure CS performance in basketball and presents different kinetic and kinematic features than LS.